Phase I dose escalation study of IO-108, an anti-LILRB2 antibody, in patients with advanced solid tumors - Ying Zhu; Tao Huang; John Powderly; Aung Naing; Manish R Patel; Matthew H Taylor; Rong Deng; Kyu Hong; Luke Chung; Hongyu Tian; Wen Hong Lin; Paul Woodard; et al. (Journal for ImmunoTherapy of Cancer)
Purpose In this first-in-human dose escalation study, the safety and efficacy of IO-108, a fully human monoclonal antibody targeting leukocyte immunoglobulin-like receptor B2 (LILRB2), was investigated in patients with advanced solid tumors as monotherapy and in combination with pembrolizumab, an anti-programmed cell death protein 1 (PD-1) antibody.Methods The study included patients with histologically or cytologically confirmed advanced and relapsed solid tumors, with measurable disease by Response Evaluation Criteria In Solid Tumors (RECIST) V.1.1. Patients were treated with escalating doses of IO-108 every 3 weeks (Q3W) as monotherapy and in combination with pembrolizumab. Safety and tolerability were the primary objectives. Secondary and exploratory objectives included: pharmacokinetics, clinical efficacy, immunogenicity and biomarkers.Results Of 25 patients enrolled, 12 were treated with IO-108 monotherapy and 13 received combination therapy. IO-108 was well-tolerated up to the maximally administered dose of 1,800 mg every 3 weeks (Q3W) as monotherapy and in combination with pembrolizumab. No dose-limiting toxicity was observed, and a maximum tolerated dose was not reached. Treatment-related adverse events (TRAEs) occurred in 6 (50.0%) patients treated with IO-108 monotherapy and 6 (46.2%) patients treated with IO-108+pembrolizumab. All TRAEs were mild or moderate (Grade 1 or 2), and no TRAEs led to treatment discontinuation or death. IO-108 exhibited a dose-proportional increase in exposure. Full receptor occupancy (RO) in peripheral blood was achieved at doses ≥600 mg. The overall response rate was 9% (1/11) in the monotherapy and 23% (3/13) in the combination therapy. A patient with treatment-refractory Merkel cell carcinoma treated with IO-108 monotherapy achieved a durable complete response (CR) for more than 2 years. Pharmacodynamic gene expression changes reflecting increased tumor infiltration of T cells were associated with clinical benefits in both monotherapy and combination therapy. Additionally, baseline tumor inflammation gene signature (TIS) scores correlated with clinical benefit.Conclusion IO-108 is well tolerated and has led to objective response as monotherapy and in combination with pembrolizumab. The complete response and the pharmacodynamic changes in the monotherapy cohort demonstrate single agent activity of IO-108 and provide proof of concept that targeting myeloid-suppressive pathways through LILRB2 inhibition may potentiate the clinical efficacy of anti-PD-1 immune checkpoint inhibitors.Trial registration number NCT05054348.